Good Governance Pada Penerapan Aplikasi Tangerang Live di Kota Tangerang - Putri, Putri Ariviani Safitri; Ralita Ayu Pratiwi; Nida Aeni; Rika; Widiana Astuti Simamora; Yunizar Fazriyanti; Risma Ramahyanti (Universitas Merdeka Madiun, 2025)
Good Governance is generally defined as the proper management of government based oncertain rules and fundamental principles. A